The other frontiers of Arab nationalism: Ibadis, berbers, and the Arabist-Salafi Press in the Interwar period - Ghazal, Amal N. (International Journal of Middle East Studies, 2010)
On Abū Isḥāq Ibr. Iṭfayyish (Cairo), Abū ‘l-Yaqẓān Ibr. (Mīzāb), Hāshil al-Maskarī and his journal al-Falaq in Zanzibar.
Keywords: Abū ‘l-Yaqẓān, Ibrāhim (1888-1973); Aṭfiyyash, Ibrāhīm b. Muḥammad (1886-1965); Maskarī, Hāshil al-; Réformisme

Islamic reform and Arab nationalism: expanding the crescent from the Mediterranean to the Indian Ocean (1880s-1930s) - Ghazal, Amal N. (Culture and civilization in the Middle East, 2010)
This book examines the relationship between Islam and nationalism and the evolution of identity politics. Bridging African and Arab histories and giving a cross-national and cross-regional analysis of movements of religious reform, nationalism and anti-colonialism, its wide geographical coverage ranges from Zanzibar on the Indian Ocean through to Oman into the Mediterranean
Keywords: Zanzibar